2x-y=7

Subtract 2x from both sides of the equation.

-y=7-2x

Multiply each term in -y=7-2x by -1

Multiply each term in -y=7-2x by -1.

(-y)⋅-1=7⋅-1+(-2x)⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=7⋅-1+(-2x)⋅-1

Multiply y by 1.

y=7⋅-1+(-2x)⋅-1

y=7⋅-1+(-2x)⋅-1

Simplify each term.

Multiply 7 by -1.

y=-7+(-2x)⋅-1

Multiply -1 by -2.

y=-7+2x

y=-7+2x

y=-7+2x

y=-7+2x

Choose any value for x that is in the domain to plug into the equation.

Remove parentheses.

y=-7+2(0)

Simplify -7+2(0).

Multiply 2 by 0.

y=-7+0

Add -7 and 0.

y=-7

y=-7

Use the x and y values to form the ordered pair.

(0,-7)

(0,-7)

Remove parentheses.

y=-7+2(1)

Simplify -7+2(1).

Multiply 2 by 1.

y=-7+2

Add -7 and 2.

y=-5

y=-5

Use the x and y values to form the ordered pair.

(1,-5)

(1,-5)

Remove parentheses.

y=-7+2(2)

Simplify -7+2(2).

Multiply 2 by 2.

y=-7+4

Add -7 and 4.

y=-3

y=-3

Use the x and y values to form the ordered pair.

(2,-3)

(2,-3)

These are three possible solutions to the equation.

(0,-7),(1,-5),(2,-3)

Find Three Ordered Pair Solutions 2x-y=7